Media and Architecture Media Effect on the Formation of Architectural Identity - Basim Hasan Al- Majidi; Ahmed Hashim Al-Aukabi; Zainab Khalid Rashad (Wasit Journal of Engineering Sciences)
The general cognitive literatures have been studied several concepts which have different effects  on the field of architecture and its basic vocabulary, such as the concept of the media and its impact in highlighting the general features of architecture of the modern era, according to reality and the available circumstances on one hand and on the establishment for a balanced and stable identity within the overall architectural field, and within formulas and many varied forms in many levels within the general theoretical cognitive framework for all of them on the other hand. The research aims to define the general principles for the cognitive vision of the concept of the media and its role and influence in the field of architecture and in the formation of architectural identity, which forms the cognitive research problem and that comes as (there is lack in clarity for the cognitive perception about the effect of the concept of media on architecture in general and its role in building and shaping the architectural identity in particular). The research methodology takes the Literatures which concern with general cognitive of the concept of the media and its relationship to the concept of architectural identity within theoretical frameworks and of specific vocabulary, then the research goes to apply these frameworks to specific applications in the field of information and analysis of the results of this application and explore the verification cases of such frameworks indicators, then introduces the final conclusions highlighted the importance of the media's role in the monitoring of issues and topics of architectural and processed through two-parts (technical and humanitarian) in order to change people's perceptions to the fact that architecture and the preservation of the identity of a society from the impact of globalization as well as the evolution towards global through equilibrium between technology and investment and between culture and traditions.